Kallikrein-related peptidase-4 (KLK4): role in enamel formation and revelations from ablated mice - Bartlett, John D.; Simmer, James P. (Frontiers in Physiology, 2014)
Enamel development occurs in stages. During the secretory stage, a soft protein rich enamel layer is produced that expands to reach its final thickness. During the maturation stage, proteins are removed and the enamel matures into the hardest substance in the body. KLK4 is expressed during the transition from secretory to the maturation stage and its expression continues throughout maturation. KLK4 is a glycosylated chymotrypsin-like serine protease that cleaves enamel matrix proteins prior to their export out of the hardening enamel layer. Mutations in KLK4 can cause autosomal recessive, non-syndromic enamel malformations in humans and mice. Klk4 ablated mice initially have normal-looking teeth with enamel of full thickness. However, the enamel is soft and protein-rich. Three findings are notable from Klk4 ablated mice: first, enamel rods fall from the interrod enamel leaving behind empty holes where the enamel fractures near the underlying dentin surface. Second, the 10,000 crystallites that normally fuse to form a solid enamel rod fail to grow together in the ablated mice and can fall out of the rods. Third, and most striking, the crystallites grow substantially in width and thickness (a- and b-axis) in the ablated mice until they almost interlock. The crystallites grow in defined enamel rods, but interlocking is prevented presumably because too much protein remains. Conventional thought holds that enamel proteins bind specifically to the sides of enamel crystals to inhibit growth in width and thickness so that the thin, ribbon-like enamel crystallites grow predominantly in length. Results from Klk4 ablated mice demonstrate that this convention requires updating. An alternative mechanism is proposed whereby enamel proteins serve to form a mold or support structure that shapes and orients the mineral ribbons as they grow in length. The remnants of this support structure must be removed by KLK4 so that the crystallites can interlock to form fully hardened enamel.